1990
DOI: 10.1073/pnas.87.4.1620
|View full text |Cite
|
Sign up to set email alerts
|

Apparent hydroxyl radical production by peroxynitrite: implications for endothelial injury from nitric oxide and superoxide.

Abstract: Superoxide dismutase reduces injury in many disease processes, implicating superoxide anion radical (02 ) as a toxic species in vivo. A critical target of superoxide may be nitric oxide (NO-) produced by endothelium, macrophages, neutrophils, and brain synaptosomes. Superoxide and NO-are known to rapidly react to form the stable peroxynitrite anion (ONOO-). We have shown that peroxynitrite has a pKa of 7.49 ± 0.06 at 3TC and rapidly decomposes once protonated with a half-life of 1.9 sec at pH 7.4. Peroxynitrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

66
3,796
6
66

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 6,484 publications
(3,934 citation statements)
references
References 31 publications
66
3,796
6
66
Order By: Relevance
“…13 Normal movements, ability to walk on a 5 mm wide bar. with the body of work describing a destructive role of iNOS in cerebral ischaemia and traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Normal movements, ability to walk on a 5 mm wide bar. with the body of work describing a destructive role of iNOS in cerebral ischaemia and traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…with the body of work describing a destructive role of iNOS in cerebral ischaemia and traumatic brain injury. NO derived from iNOS catalytic activity may react with the superoxide anion to form peroxynitrite, 9 a molecule that is associated with oxidative tissue damage 13 and apoptotic neuronal death. 14 In contrast to this, other investigators have shown that functional end points after controlled cortical impact brain trauma were significantly worsened if iNOS was pharmacologically inhibited or genetically deficient in experimental rats and mice, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…•- [21], can be produced solely by the action of XOR [19]. The XORderived ONOO -has been proposed as a bactericidal agent in milk and the digestive tract [19].…”
Section: Introductionmentioning
confidence: 99%
“…Additional work has demonstrated that the infusion of PN at levels that mimic the estimated concentration produced in the contused spinal cord produces nitrative immunostaining and neuronal damage similar to that produced by contusion injury (Liu et al, 2005). The increase in 3-NT is paralleled by increases in LP products (Xiong et al, 2007) and the activation of the DNA repair enzyme poly-ADP ribose polymerase (Scott et al, 1999; Scott et al, 2004); both of these pathochemical events are known to be capable of being produced by PN (Beckman et al, 1990; Beckman, 1991; Beckman, 2002; Pacher et al, 2007; Radi et al, 1991). A recent report from our laboratory has shown that the coincident increase in the levels of 3-NT and the LP product 4-HNE during the first hour after injury persists at least until 7 days post-injury (Xiong et al, 2007).…”
Section: Discussionmentioning
confidence: 99%